PREDATORY STATE-ETHNO REGIONAL RELATIONS, PARASITIC OLIGARCHIC CLASS AND THE RESTRUCTURING QUESTION IN NIGERIA: HOW ETHICAL? - Abada , Ifeanyichukwu Micheal; Okafor, Nneka Ifeoma; Udeogu , Celestine Uchechukwu (PEOPLE: International Journal of Social Sciences, 2018)
The state, according to Marxian class analysis, is supposed to be an independent and neutral force, standing above all societal forces. Its relations with the society are to maintain order and to treat all sections of the political society on the principles of equity and equality, being a product of a social contract arising from the people. However, the Nigerian state, due to its colonial descent and mission, sowed the seed of disorder by taking side with a section of the society. Determined to leverage one region against another, the state became partisan, exploitative and predatory in character and principle. From the favoured region has emerged a parasitic class, feeding fat on the resources and pains of other regions. Being the beneficiary of state predation, the class has constituted itself into a guardian class for the preservation of the predatory state structure. Consequently, this perceived odious political structure has attracted the concerns of other sections of the country, whose insistence is on having the structure restructured so as to enable each region or zone take its fates into its hands. Four out of the six zones into which the country is divided have lent their support to restructuring, while two (the zones of the parasitic oligarchic class) are in vehement opposition to it. In analogous terms, their opposition is informed by the fear of a parasite losing its host, which corresponds to death.